Reflections on Academic Leadership: Between Innovation, Resistance, and Students Freedom - Samsu Armadi; Bahrani Bahrani (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2025)
Changes in academic leadership often bring complex dynamics. The author's experience as head of a study program provided a space for reflection on how innovation can trigger internal resistance when different paradigms collide. Efforts to provide academic freedom to students—especially in determining thesis topics and types of research—became a point of friction with some lecturers who still maintained old patterns. This article explores these empirical experiences in a narrative-analytical format, combining personal reflections with theoretical frameworks on academic leadership, scientific freedom, and the dynamics of university bureaucracy. Using a reflective qualitative approach, the article outlines five main focuses: innovation, resistance, internal conflict, leadership under pressure, and academic freedom as a student right. The findings suggest that innovation often requires challenging negotiations within organizational culture, while resistance can open the door to more constructive dialogue when managed appropriately. The article concludes with recommendations for strengthening more supportive, adaptive, and humanistic academic leadership.